Pengaruh Fasilitas Kerja, Motivasi Intrinsik, dan Disiplin Kerja Terhadap Kinerja Pegawai (Studi pada Dinas Pariwisata Daerah Istimawa Yogyakarta) - Albertus Leopoldus Odem; Kusuma Chandra Kirana; Epsilandri Septyarini (Jurnal Ilmiah Universitas Batanghari Jambi, 2023)
The research aims to examine whether the performance of DIY Tourism Office employees is influenced by intrinsic motivation, work discipline, and the influence of the work environment. The variables analyzed in this study were employee performance (Y), intrinsic motivation (X2), work discipline (X3), and workplace facilities (X1). This study uses a quantitative approach because the research data is numerical and statistical analysis is carried out. A total of 50 DIY Tourism Office employees participated in this study. The entire sample of this study is the DIY Tourism Office workers. By using saturated sampling and non-probability sampling, this study involved the entire population of 50 Yogyakarta tourism office employees. Workplace facilities (X1) have a positive and significant effect on employee performance (Y), according to the results of the analysis. Employee performance (Y) is completely unaffected by intrinsic motivation (X2), according to the analysis. Employee performance (Y), as well as work discipline (X3), are all positively and significantly influenced by workplace facilities, intrinsic motivation, and work discipline. DIY Tourism Office employee performance is positively and significantly influenced by intrinsic motivation, work discipline, and the influence of the work environment.